Design of an Active Anti-Roll Bar for Off-Road Vehicles - S. Gosselin-Brisson; M. Bouazara; M.J. Richard (Shock and Vibration)
This paper presents a comparison of performance between a passive and an active anti-roll bar. Off-road vehicles are subject to large input road motion and appreciable lateral forces, making anti-roll bars desirable. A four DOF linear model is used to represent an independent suspension and to design the controller. For every case the performance is evaluated for severe road input perturbation and lateral acceleration. A method is presented to illustrate the compromise between stability and comfort inherent in passive anti-roll bar selection. This method was used to select a realistic anti-roll bar stiffness. The active anti-roll bar was designed using full state feedback optimal controller. A simplification of the active system is proposed to reduce the number of measurements and eliminate the need for an optimal observer. The results show a superior performance in ride and handling for the active controller in the frequency range of interest. The addition of filters is proposed to maximize controller efficiency and to reduce associated problems.